The Contribution of Indigenous State Apparatus in Building the Community of Ureng Country - Laitupa, Patma Sari; Abas, Aisa; Tuharea, Jumiati (CV. Rayyan Dwi Bharata, 2023)
Village development is an activity that covers all aspects of life in village society. Negeri Adat is a customary law community unit that is territorial genealogical in nature which has territorial boundaries, which has the authority to regulate and manage the interests of the local community based on the rights of origin and local customs which are recognized and respected within the system of government of the unitary State of the Republic of Indonesia. Every development activity carried out by government staff must be notified to the Saniri and also in the implementation of the development there must be a discussion or exchange of opinions by the government staff with the traditional land apparatus, namely the Saniri. The writing of this thesis discusses